Konseling Kelompok Untuk Mengurangi Simptom Stres Pada Guru Pendamping Anak Berkebutuhan Khusus - Fitria Rachmawaty (University of Merdeka Malang, 2015)
This study focuses on the application of group counseling on stress reduction of assistant teacher for children with special needs. The subjects of this study is 6 assistant teacher for children with special needs, consist of 5 female and 1 male assistant teacher. The subjects showed symptoms of stressduring the time they became educators in elementary school M. Subjects age ranged from 20 years to 29 years. The data collection technique used on this study are observationand interview. Interventions were performed using group counseling basic client centered therapy technicques. The result obtained is that each member of the group is able to identify the source of their stressand the impact of the stress to their life, and has a relatively different way in minimalizing the stress level.